Towards integrating imaging and immunology in glioblastoma: mapping blood immune system metrics to tumor magnetic resonance image data - Johanna Heugenhauser; Carmen Visus; Johanna Buchroithner; Christine Marosi; Karl Rössler; Thomas Felzmann; Georg Widhalm; Sarah Iglseder; Martha Nowosielski; Friedrich Erhart (Acta Neuropathologica Communications)
Abstract Background Glioblastoma is the most frequent and aggressive brain cancer. It is a highly immunology-driven disease as up to a third of its mass is composed of immune cells. Apart from immunology, imaging is a major research frontier. The VASARI (Visually AcceSAble Rembrandt Images) MRI feature set is a system designed to enable consistent description of gliomas using a set of defined visual features and controlled vocabulary. Even though imaging and immunology are both indispensable for glioblastoma phenotyping, a comprehensive integration of these two disciplines has not been performed so far. Material and methods 76 patients from a previous glioblastoma immunotherapy clinical trial were retrospectively screened for the availability of peripheral blood immunology and tumor imaging data at baseline, i.e. at the start of the study. For 41 patients both were available. MRI were then analyzed via volumetry and VASARI morphometry. The resulting 27 imaging variables were linked with 67 peripheral blood immunology variables from flow cytometry and PCR and all potential relations were mapped. Results In an initial broad screening, 94 imaging-immunology associations were discovered. Notably, features of the contrast-enhancing margin like its thickness and its shape were positively correlated with various T cell species including activated cytotoxic CD8+ T cells and central memory CD8+ T cells. The T2-volume was correlated with CD56+CD16− natural killer cells, and the necrosis volume was correlated with immunopolarizing mRNAs in the blood (IFN-γ, GATA3, ROR-gt). After multiple testing correction, two imaging-immunology associations were confirmed as significant: a thick contrast-enhancing margin was correlated with lower regulatory T cell markers in the blood and invasion of deep white matter was correlated with less T helper 17 factors. Conclusion We here provide first evidence that imaging and peripheral blood immunology features can go hand in hand and that imaging variables can correlate with systemic immunophenotypes. Especially a thick contrast-enhancing margin seems to indicate a pro-inflammatory immune state. Via pioneering the integration of imaging and immunology, we not only advance basic glioblastoma science but we also open up novel avenues for research. In the future, e.g. patient stratification for therapy development could be based on imaging-guided immunophenotyping.